The professional development of teachers for the attention of students with intellectual disabilities in Belize - Armstrong, Deserie Idele; Conill Armenteros, Julio Antonio; Salabarría Márquez, María Cristina (My University, 2022)
The improvement of the Primary Education teacher for the educational care of students with intellectual disabilities, constitutes a priority of the Ministry of Education in Belize, which presupposes, from the legal framework, access to education for all students, including those who have special educational needs. This has led to the need to influence teachers so that they raise the quality of their work and can specify the educational response in accordance with the needs of each student. The deepening of the study led to the need for its treatment and to offer a response to this problem, so it is proposed as an objective to present the foundation of a theoretical-methodological conception for the improvement of Primary Education teachers on educational care required by learners with intellectual disabilities in Belize. In the research process, theoretical, empirical and statistical methods were applied, which made it possible to collect, interpret and process the information related to the object of study, in order to offer a solution to the identified scientific problem. The theoretical-methodological conception is based on two guiding ideas that promote the improvement of the teacher in terms of educational attention and its link with the methodological work to favor the performance of their work with students with intellectual disabilities. The evaluation by expert criteria allowed to verify the correlation between the theoretical and methodological value, revealing its feasibility in terms of favoring the teacher's improvement.
Keywords: professional development; teacher development; primary education; intellectual disabilities; special needs